2017
DOI: 10.3847/1538-4357/aa6aa8
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Helicity Estimations in Models and Observations of the Solar Magnetic Field. III. Twist Number Method

Abstract: We study the writhe, twist and magnetic helicity of different magnetic flux ropes, based on models of the solar coronal magnetic field structure. These include an analytical force-free Titov-Démoulin equilibrium solution, non forcefree magnetohydrodynamic simulations, and nonlinear force-free magnetic field models. The geometrical boundary of the magnetic flux rope is determined by the quasi-separatrix layer and the bottom surface, and the axis curve of the flux rope is determined by its overall orientation. T… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(68 citation statements)
references
References 57 publications
(116 reference statements)
1
64
0
2
Order By: Relevance
“…In the movie associated with Figure 2, it is possible to see that the flows trace the curvilinear paths of the fanning field lines from ≈ 01:30 UT until eruption. As we have assumed a fluxrope configuration of the magnetic environment surrounding and suspending the filamentary material, by studying the magnetic topology of simulations by authors such as Roussev et al (2003), Mei et al (2017), and Guo et al (2017), it is difficult to reconcile how the highly twisted field lines of these studied flux ropes could produce the observed linear-like motions of plasma; plasma-β (plasma pressure/magnetic pressure) is low in the corona and therefore charged material is line-tied. Interestingly, extrapolations of less strongly twisted flux ropes, such as those by Su et al (2011) andJiang et al (2014), are easier to compare to the observations as they contain very weakly twisted field lines that pass through the axes of the extrapolated flux ropes.…”
Section: Discussionmentioning
confidence: 99%
“…In the movie associated with Figure 2, it is possible to see that the flows trace the curvilinear paths of the fanning field lines from ≈ 01:30 UT until eruption. As we have assumed a fluxrope configuration of the magnetic environment surrounding and suspending the filamentary material, by studying the magnetic topology of simulations by authors such as Roussev et al (2003), Mei et al (2017), and Guo et al (2017), it is difficult to reconcile how the highly twisted field lines of these studied flux ropes could produce the observed linear-like motions of plasma; plasma-β (plasma pressure/magnetic pressure) is low in the corona and therefore charged material is line-tied. Interestingly, extrapolations of less strongly twisted flux ropes, such as those by Su et al (2011) andJiang et al (2014), are easier to compare to the observations as they contain very weakly twisted field lines that pass through the axes of the extrapolated flux ropes.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the sum of the twist and writhe is closer to being independent from the choice of the plane used to determine the axis (as expected; Török et al 2010). Guo et al (2017) concluded that a good proxy of the magnetic helicity in the current-carrying field inside a finite volume is…”
Section: Twist and Writhementioning
confidence: 99%
“…To quantify the twist in our very asymmetric case, the twist of individual field lines in the flux rope was calculated around an axis, and the average was taken (Guo et al 2010(Guo et al , 2013. Following Guo et al (2017), the axial field line is defined as the field line with the smallest ratio of tangential-to-normal magnetic field components with respect to a plane roughly perpendicular to the body of the flux rope.…”
Section: Twist and Writhementioning
confidence: 99%
“…Apart from field line helicity there are other methods that employ the magnetic connectivity to compute quantities related to magnetic helicity. An example is the twist number method (Guo et al 2017), where the twist component of helicity is computed in configurations consisting of twisted magnetic flux ropes. In an alternative method that approximates helicity through its twist, Malanushenko et al (2011) compute RMH by matching the shapes of coronal loops with field lines of a linear force-free field.…”
Section: Introductionmentioning
confidence: 99%